STRATEGI PENINGKATAN KOMPETENSI KEWIRAUSAHAAN DALAM MEMBENTUK JIWA ENTREPRENEURSHIP MAHASISWA (STUDI KASUS PADA ORGANISASI FORMA KIP-K UIN RADEN INTAN LAMPUNG) - Yola Dwi Patrica; Yetri; Nina Ayu Puspita Sari; Riyuzen Praja Tuala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the strategy for improving entrepreneurial competency in developing students entrepreneurial spirit (a case study of the FORMA KIP-K organization at UIN Raden Intan Lampung), and to identify the obstacles encountered during the process. This study uses a qualitative descriptive approach with observation, interview, and documentation data collection techniques. The focus of this study covers five aspects, namely the strategies used in workshops, training and development, collaboration (networking), mentoring and approaches to job training. The results show that FORMA KIP-K students have high potential but have not been optimally facilitated with strategies. Therefore competency improvement strategies are crucial in developing students entrepreneurial spirit in the organization.